EVALUATION OF PERFORMANCE OF ASYMMETRICALLY DUAL SYSTEM STRUCTURES USING PUSHOVER AND TIME HISTORY ANALYSES - Kurdian Suprapto; Sudarto Sudarto (Journal of Civil Engineering, 2009)
Performance-based design is becoming increasingly popular in designing a seismic resistant building. In the study, a twelvestory, reinforced concrete office building with asymmetric configuration using dual system located in seismic zone 6 was designed conforming to the Indone sian S e i smi c Code SNI 03-1726-2002 and the Indonesian Concrete Building Code SNI 03-2847-2002. The seismic performance of the building was evaluated using the Static Nonlinear (Pushover) Analysis and Inelastic Dynamic Time History Analysis. The performance point obtained from the pushover analysis was defined using various methods, such as FEMA 356, ATC-40, FEMA 440, and SNI 03-1726-2002. The result of the study indicated that the highest performance point was that obtained according to FEMA 356 and FEMA 440, whereas the lowest value was that in accordance with SNI-03-1726-2002. The roof displacement difference of that obtained from El-Centro dynamic analysis and performance-point pushover analysis can reach up to 5 cm and 2.4 cm in X- and Y-directions, respectively. This indicates that the pushover analysis is quite accurate for evaluating the corresponding building since the first mode shape is quite dominant.